A solution to salinity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The problem of saline water is inceasing in ACP agricultural production. Already half of the world s groundwater resources are saline, and on almost half of the world s irrigated land salinity is limiting production. Even if today in most...